2021
DOI: 10.3390/agriculture11111148
|View full text |Cite
|
Sign up to set email alerts
|

Durum Wheat Mediterranean Landraces: A Valuable Source for Resistance to Tan Spot Disease

Abstract: Tan spot (TS), caused by Pyrenophora tritici-repentis (Ptr), has gained significant importance in Tunisia. In this study, a Mediterranean durum wheat collection of 113 accessions were evaluated under field conditions, during the 2018–2019 cropping season, for resistance to Ptr at Koudia experimental station in Bou Salem (Tunisia). The disease progress curve (AUDPC) was used to screen this collection, and the effect of days to heading (DH) and plant height (PH) were evaluated in relation to TS resistance. No si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 83 publications
1
14
0
Order By: Relevance
“…A variability in reactions to TS was observed between genotypes at both seedling and adult stages; several phenotypic classes were established (R, MR, MS, and S) and novel sources of resistance to TS were identified. The comparison of seedling and adult resistance revealed a highly significant correlation, similar to a recent study by Laribi et al [ 14 ] under the same conditions, and to other studies [ 51 , 52 , 53 , 54 ]. During the testing period (2018–2019), 69% of accessions remained R-MR at both growth stages; therefore, screening for tan spot disease resistance at the seedling stage can allow for the elimination of most susceptible materials, avoiding costly and lengthy confirmations of field resistance as well as allowing one to reduce the number of accessions to be further tested in replicated field trials.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…A variability in reactions to TS was observed between genotypes at both seedling and adult stages; several phenotypic classes were established (R, MR, MS, and S) and novel sources of resistance to TS were identified. The comparison of seedling and adult resistance revealed a highly significant correlation, similar to a recent study by Laribi et al [ 14 ] under the same conditions, and to other studies [ 51 , 52 , 53 , 54 ]. During the testing period (2018–2019), 69% of accessions remained R-MR at both growth stages; therefore, screening for tan spot disease resistance at the seedling stage can allow for the elimination of most susceptible materials, avoiding costly and lengthy confirmations of field resistance as well as allowing one to reduce the number of accessions to be further tested in replicated field trials.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies on Pyrenophora tritici-repentis in Tunisia revealed high phenotypic and genotypic diversity of Ptr in Tunisia. Hence, phenotyping wheat populations from the Mediterranean region under favorable conditions can lead to the discrimination between resistant and susceptible accessions [ 14 , 19 , 24 , 25 ]. In this study, 549 wheat accessions that comprised mainly landraces from five Mediterranean countries were assessed for resistance/susceptibility to TS disease in Tunisia over two cropping seasons at the adult stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations